Potential Source Rock of Albian of the Benin Coastal Sedimentary Basin - KIKI, Armand; KAKI, Christophe; d’ALMEIDA, Gérard Alfred Franck (My University, 2018)
Albian sediments represent the upper unit of Lower Cretaceous deposits only present in the offshore part of the coastal sedimentary basin of Benin which belongs to the Dahomey Embayment, a province with high hydrocarbon potential. The study of the particularities and potential source rocks of the Albian deposits is based on logging data and rock samples from five oil wells drilled in the offshore basin. The study methodology focused on Gamma Ray (GR) logging analysis. Rock-Eval pyrolysis assessment of clay sediments of this formation and their petrography. The analysis of the GR profiles of the various wells made it possible to release sandstone and clay levels within the Albian formation. Potential source rock indicated by gamma ray are silty-clay and silty-clayey sediments with high granularity and varied vegetable detritus content (organic matter). The average values obtained during the Rock-Eval pyrolysis of the sampled levels are 3.01% for the TOC and 6.04 mgHC/g for the S2 while those for the maximum temperature (Tmax) and the d Hydrogen (IH) are respectively between 321 and 465°C and between 29 and 362 mgHC/gTOC. These results indicate that the Albian Formation is a good to very good, mature, late-maturing, oil potential parent rock that contains Type III, II and II/III kerogen.
Keywords: Albian sediment; Coastal sedimentary basin of Benin; Gamma ray; Pyrolysis Rock-Eval 6; Source rock